Fagonia indica Repairs Hepatic Damage through Expression Regulation of Toll-Like Receptors in a Liver Injury Model - Fareeha Azam; Nadeem Sheikh; Gibran Ali; Asima Tayyeb (Journal of Immunology Research)
Fagonia indica is a traditionally used phytomedicine to cure hepatic ailments. However, efficient validation of its hepatoprotective effect and molecular mechanisms involved are not yet well established. Therefore, the present study was designed to evaluate the hepatoprotective activity of Fagonia indica and to understand the molecular mechanisms involved in the reversal of hepatic injury. The liver injury mouse model was established by thioacetamide followed by oral administration of plant extract. Serum biochemical and histological analyses were performed to assess the level of hepatic injury. Expression analysis of proinflammatory, hepatic, and immune regulatory genes was performed with RT-PCR. Results of serological and histological analyses described the restoration of normal liver function and architecture in mice treated with plant extract. In addition, altered expression of proinflammatory (IL-1β, IL-6, TNF-α, and TGF-β) and hepatic (krt-18 and albumin) markers further strengthens the liver injury reversal effects of Fagonia indica. Furthermore, a significant expression regulation of innate immunity components such as toll-like receptors 4 and 9 and MyD-88 was observed suggesting an immune regulatory role of the plant in curing liver injury. In conclusion, the current study not only proposes Fagonia indica, a strong hepatoprotective candidate, but also recommends an immune regulatory toll-like receptor pathway as an important therapeutic target in liver diseases.